Long-term renal outcome in children with OCRL mutations: retrospective analysis of a large international cohort. Issue 1 (5th October 2016) - Zaniew, Marcin; Bökenkamp, Arend; Kołbuc, Marcin; La Scola, Claudio; Baronio, Federico; Niemirska, Anna; Szczepańska, Maria; Bürger, Julia; La Manna, Angela; Miklaszewska, Monika; Rogowska-Kalisz, Anna; Gellermann, Jutta; et al.
Abstract: Background: Lowe syndrome (LS) and Dent-2 disease (DD2) are disorders associated with mutations in the OCRL gene and characterized by progressive chronic kidney disease (CKD). Here, we aimed to investigate the long-term renal outcome and identify potential determinants of CKD and its progression in children with these tubulopathies. Methods: Retrospective analyses were conducted of clinical and genetic data in a cohort of 106 boys (LS: 88 and DD2: 18). For genotype–phenotype analysis, we grouped mutations according to their type and localization. To investigate progression of CKD we used survival analysis by Kaplan–Meier method using stage 3 CKD as the end-point. Results: Median estimated glomerular filtration rate (eGFR) was lower in the LS group compared with DD2 (58.8 versus 87.4 mL/min/1.73 m 2, P < 0.01). CKD stage II–V was found in 82% of patients, of these 58% and 28% had moderate-to-severe CKD in LS and DD2, respectively. Three patients (3%), all with LS, developed stage 5 of CKD. Survival analysis showed that LS was also associated with a faster CKD progression than DD2 (P < 0.01). On multivariate analysis, eGFR was dependent only on age ( b = −0.46, P < 0.001). Localization, but not type of mutations, tended to correlate with eGFR. There was also no significant association between presence of nephrocalcinosis, hypercalciuria, proteinuria and number of adverse clinical events and CKD. Conclusions: CKD is commonly found in children with OCRL mutations. CKD progression was strongly related to the underlying diagnosis but did not associate with clinical parameters, such as nephrocalcinosis or proteinuria.